2011
DOI: 10.1016/j.ajpath.2010.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 in Breast Cancer Stroma Fibroblasts Regulates Extracellular Matrix Fiber Organization and Carcinoma Cell Motility

Abstract: Stromal fibroblasts of breast carcinomas frequently express the cell surface proteoglycan syndecan-1 (Sdc1). In human breast carcinoma samples, stromal Sdc1 expression correlates with an organized, parallel, extracellular matrix (ECM) fiber architecture. To examine a possible link between stromal Sdc1 and the fiber architecture, we generated bioactive cell-free three-dimensional ECMs from cultures of Sdc1-positive and Sdc1-negative murine and human mammary fibroblasts (termed ECM-Sdc1 and ECM-mock, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 55 publications
3
128
0
Order By: Relevance
“…However, the mechanism in which syndecan-1 is implicated in breast cancer is still unclear, although studies have shown that induction of syndecan-1 in stromal fibroblasts stimulates breast cancer cell growth, (20) regulates extracellular matrix fibre organisation and malignant cell motility, (21) as well as enhances tumour angiogenesis. (22) Syndecan-1 has also been reported to have more intense staining of the stromal component of breast cancer tissue compared to normal breast tissue, (23) in keeping with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism in which syndecan-1 is implicated in breast cancer is still unclear, although studies have shown that induction of syndecan-1 in stromal fibroblasts stimulates breast cancer cell growth, (20) regulates extracellular matrix fibre organisation and malignant cell motility, (21) as well as enhances tumour angiogenesis. (22) Syndecan-1 has also been reported to have more intense staining of the stromal component of breast cancer tissue compared to normal breast tissue, (23) in keeping with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, removal of 6-O sulphates can reduce tumour growth in vivo (Narita et al 2006), and HSPGs from normal versus malignant epithelial cells show differences in their ability to support FGF-2/FGFR complex formation (Mundhenke et al 2002). Stromal fibroblasts expressing high levels of syndecan-1, a HSPG core protein, enhanced the attachment of breast carcinoma cells and the establishment of cancer microenvironment permissive to the cancer cell migration and invasion (Yang et al 2011). Basement membranes of renal cell carcinomas show altered ability to bind to members of the FGF family in an HS-dependent manner (Friedl et al 1997).…”
Section: Hspg In Disease Mechanismsmentioning
confidence: 99%
“…In contrast, the previously reported in vitro breast cancer models were not evaluated for their batch-to-batch reproducibility. The use of rotary bioreactors to carry out co-cultures of breast cancer cells and fibroblasts under defined and stringent culture conditions offered several distinct advantages over the traditional 3-D co-cultures on xenogenically derived gel matrix, which were used in the previously reported studies (Gudjonsson et al 2002(Gudjonsson et al , 2003Sung et al 2009;Bauer et al 2010;Han et al 2010;Inman and Bissell 2010;Beliveau et al 2011;Yang et al 2011;Sung et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such a model, representing major cellular components of the breast tumor microenvironment, may serve as a basis Gudjonsson et al 2002;Seidl et al 2002;Sung et al 2008;Hsaio et al 2009;Han et al 2010;Beliveau et al 2011;Sung et al 2011;Yang et al 2011. for the study of molecular mediators of cancer progression, which promote malignant growth, angiogenesis, metastasis, and reduced apoptosis.…”
Section: Discussionmentioning
confidence: 99%